2015
DOI: 10.1039/c5dt01771h
|View full text |Cite
|
Sign up to set email alerts
|

Accessing perfluoroalkyl nickel(ii), (iii), and (iv) complexes bearing a readily attached [C4F8] ligand

Abstract: The [C4F8] ligand was shown to support well-defined terpyridyl nickel complexes in the +2 and +3 oxidation states. Notably, a cyclic voltammetry study of the nickel(iii) species indicates that an additional oxidation is accessible, providing a family of related fluoroalkyl nickel complexes spanning the +2 to +4 oxidation states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 39 publications
1
66
0
Order By: Relevance
“…It was found that the addition of terpyridine to [Ni(MeCN)2(C4F8)] 12 led cleanly to the formation of [Ni(tpy)(C4F8)] 14 (Scheme 9) [55]. Surprisingly, in the solid state, the terpyridine ligand in 14 coordinates to nickel in a η 2 -fashion.…”
Section: Electrochemistry and Character Of The Trivalent Species [Ni(mentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the addition of terpyridine to [Ni(MeCN)2(C4F8)] 12 led cleanly to the formation of [Ni(tpy)(C4F8)] 14 (Scheme 9) [55]. Surprisingly, in the solid state, the terpyridine ligand in 14 coordinates to nickel in a η 2 -fashion.…”
Section: Electrochemistry and Character Of The Trivalent Species [Ni(mentioning
confidence: 99%
“…Terpyridine is known to bind to more than one metal center [56][57][58][59][60][61], but 13 represented the first such adduct with nickel. [55]. Surprisingly, in the solid state, the terpyridine ligand in 14 coordinates to nickel in a η 2 -fashion.…”
Section: Electrochemistry and Character Of The Trivalent Species [Ni(mentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the mechanism of HOR on the anode side of the FC,t he compound was investigated using electron spin resonance (ESR). ESR proved to be an effective methodf or the exact magnetic resonance identification of free radicals [24,25] and transition metal ions in solutions, [26] for studies of classical micellar solutions of surfactants, [27] amphiphilic calix [4]arenes, [28] andf or intermediates of ESR electrochemical transformations. [29][30][31][32][33][34][35] In order to study the nature of the reduced forms of the catalytic complex the complex was studied using ESR during reduction by molecular hydrogen and the electrochemical reduction at the potential of the first peak.…”
Section: Resultsmentioning
confidence: 99%
“…Fortuitous crystallization in MeCN/Ether provided X-Ray quality crystals. 19 S7 . 2 The [Cu(CF3)4]core was described as having "surprising" 2 stability as it possessed a rare and formally copper(III) center.…”
Section: Generation Of [Pph4]2[( 2 -So4)ni IV (Cf3)4] (8)mentioning
confidence: 99%